Pengetahuan, Sikap dan Keterampilan Masyarakat Kota Jayapura dalam Pencegahan Penularan Covid-19 - Sepo Nawipa; Rima Nusantriani Banurea; Fitrine Christiane Abidjulu (PT FORMOSA CENDEKIA GLOBAL, 2022)
The non-natural disaster status of the COVID-19 Pandemic in Papua Province has been raised from Emergency Alert to Emergency Response. People in Papua, especially those in Jayapura, are required to quarantine and practice Social Distancing and Physical Distancing. But what are the knowledge, attitudes and skills of the Jayapura people to prevent the transmission of this virus? This study was designed to look at the efforts of the Jayapura community in preventing the transmission of COVID-19 through descriptive quantitative methods. With the Google Form questionnaire data collection tool which was distributed online to the people of Jayapura, there were 117 residents of Jayapura City who became respondents in this study. The results obtained are the knowledge, attitudes and skills of Jayapura residents in preventing Covid-19 above 50%. This is because the local government is responsive and there is a national event in Jayapura that encourages a fairly fast and significant process of behavior change.